High-achieving, low-income students' perspectives of how schools can promote the academic achievement of students living in poverty. (November 2019) - Williams, Joseph M; Greenleaf, Arie T; Barnes, Erin F; Scott, Tracey R
Children and adolescents from low-income families now comprise a majority of public school students nationally. As the number of students from low-income backgrounds increases, so does the achievement gap between them and their wealthier peers. This phenomenological qualitative study examined a national sample of high-achieving, low-income middle school students' ( N  = 24) perspectives on what schools can do to promote the academic achievement of students from low-income backgrounds. Three main themes and seven subthemes were identified: create a culture of hope, develop relational networks, and establish meaningful parent–school collaborations. Implications for counselors and educators serving youth living in poverty are discussed.